Nutrition for Health and Fitness: Sugar and Other Sweeteners - Linda B. Bobroff (EDIS)
This new 8-page publication of the UF/IFAS Food Science and Human Nutrition Department provides information about sugars and other sweeteners in the American diet. It describes hidden sources of added sugars in foods to help those who want to reduce sugar intake find the added sugars in their diets. The section on high-intensity sweeteners looks at the characteristics of each approved sweetener, including aspartame, sucralose, and stevia. Written by Linda Bobroff. https://edis.ifas.ufl.edu/fs406